Regulasi Emosi Siswa Penyalahgunaan Alkohol - Asriyani M. Arifin (Peneliti.net, 2022)
This research is quantitative and employs a survey method. The study was conducted at SMA N 6 TidoreKepulauan. The subjects of the study were 130 respondents. Based on the results of data analysis using SPSS with the rank-order correlation technique (Sprearman's Rho Rank-order Correlation), a correlation coefficient value of -0,834 was obtained. The conclusion of the study is that emotional regulation variables have a relationship with alcohol abuse. The value of the negative correlation coefficient indicates the direction of the relationship, namely that the higher the level of emotional regulation, the lower the level of alcohol abuse, and vice versa. The emotion regulation variable is a variable that affects alcohol abuse. For this reason, it is necessary to take precautions so that high school students do not fall into alcohol abuse behaviors. Students are expected to be able to manage negative emotions by better understanding the emotions felt and being able to express them appropriately.